ANALISIS KENDALA PENERAPAN PROGRAM KURIKULUM 2013 PADA KELAS 2 SD NEGERI 1 JOMBOR - Lestari, Nurma Dwi; Budiman, Muhammad Arief; Setianingsih, Eka Sari (Elementary School Teacher and Education (PGSD), Faculty of Teacher Training and Education, 2019)
The purpose of this research was to describe the difficulty experience in the implementation of the 2013 curriculum in class II SD Negeri 1 Jombor in the learning process. This research is motivate by the learning process that takes place in Class II of SD N 1 Jombor by using the 2013 Curriculum is not running well, most students still cannot understand the learning material available in the given textbook. This research used a qualitative research method with a descriptive approach and by using questionaire and interview methods. After conducting the research, the results obtained were the readiness of the teacher in teaching using Curriculum 2013 which included the allocation of time in the implementation of learning, the delivery of learning and assessment materials. Besides the research experienced by students when implementing learning using Curriculum 2013 was the level of understanding of students towards learning materials that are different between one another